The anthropological meaning of marriage: main lines - Mari, Giuseppe (Central European Journal of Educational Research, 2020)
Marriage is a deeply rooted institution, but today it is in big crisis. In Italy – with regard to 2015, the latest available survey – 194,377 marriages were celebrated (246,613, in 2008), but separations were 91,706 (84,165 in 2008) and divorces 82,469 (54,351 in 2008). It is a trend in line with European data. Is marriage only an "archaeological" residual? Actually, also today the fascination of marriage survives as it is confirmed in many books on the theme and within the media where, even when the marriage takes place between subjects who have experienced the previous failure, it is described as if it were the first and the last. Of course, so many cohabitations out of marriage are related to a change of mentality, but not so deep to reject marriage as public institution. My short contribution (recently I published a book on the issue) aims to support the challenge of love in the perspective of marriage. In my opinion, the mistake about freedom could be the cause of current fragility, and education to marriage could be the possible strategy to face the problem. I start by focusing on the anthropological depth of the institution of marriage, whose recognition supports the motivation to preserve and promote the value of the wedding.